Upaya Perlindungan Hukum bagi Pihak Ketiga yang Asetnya Termasuk dalam Harta Pailit - Violenza Alif; Ali Abdullah; Dian Purwaningrum (Jurnal Hukum Lex Generalis, 2025)
Such actions by the curator could potentially fall under the category of unlawful acts (PMH) as stipulated in Article 1365 of the Civil Code. These actions are considered unlawful if they are carried out without a clear legal basis and without adequate verification of ownership. To be declared an unlawful act, the following elements must be fulfilled: the existence of an act, the act is unlawful, there is fault, loss has been incurred, and there is a causal relationship between the act and the loss incurred. This phenomenon indicates a gap between norms and practices in the administration of bankruptcy. The definition of the descriptive analytical method is a method that serves to describe or provide an overview of the object being studied through data or samples that have been collected as they are, without conducting analysis and making conclusions that apply to the general public. The curator's action of including third-party assets in the bankruptcy estate without a valid legal basis constitutes an unlawful act (PMH). This action violates the principles of property rights protection and legality in civil and bankruptcy law. The curator must ensure that the assets included in the bankruptcy estate truly belong to the debtor based on strong and valid legal evidence. Legal protection for third parties whose assets are included in the bankruptcy estate can be sought through commercial court proceedings, such as other lawsuits (Article 217 of the Bankruptcy Law) or third-party opposition (derden verzet). Third parties acting in good faith can submit proof of legal ownership through official documents such as a Sale and Purchase Agreement (PPJB), Deed of Sale and Purchase (AJB), or proof of full payment for the disputed object. Supreme Court Decision Number 311 K/Pdt.Sus–Pailit/2024 shows that the Supreme Court is increasingly consistent in providing protection for the property rights of third parties who have no debt relationship with the bankrupt debtor. This sets an important precedent in bankruptcy practice in Indonesia to prevent curators from exceeding their authority.